Fashion Films as a Particular Content of Fashion Marketing: An Analysis of its Nature in the Context of Hybrid Messages (2019)
Brands must provide valuable content that can attract attention of their audiences to generate positive results regarding their communication objectives. This becomes much more relevant in the fashion industry, where the construction of symbolic value ---even more so than the product’s exclusivity--- is essential to relate oneself emotionally with a consumer of aspirational nature. Currently, traditional advertising, which is a paradigm of the push model, is no longer efficient to reach the public. Given this, hybrid messages have become particularly relevant, and specially the fashion film as a kind of audiovisual content that is typical of fashion marketing. In order to identify the concepts that draw near to fashion films, this research began with an exhaustive literature review of, on the one hand, product placement as a type of advertising and, on the other hand, of content marketing, advertainment and branded entertainment as types of branded content. Thus, after an analysis of different hybrid messages that could host the fashion film category, features that lead to the conclusion that the subject matter responds not only to advertainment, but also to branded entertainment. Although, given the particularities of the fashion industry, within the latter it is necessary to admit the irreparable presence of products in history, as long as they do not take part in the narrative when they are exposed in a leading way, but rather establish themselves as objects of embellishment of the characters.